HUBUNGAN PENGETAHUAN DAN ASUPAN ZAT GIZI DENGAN STATUS GIZI SISWA SMAN 12 KOTA KUPANG. - Alberth M. Bau Mali; Agustina Setia; Patrisia M. Boleng (Poltekkes Kemenkes Kupang, 2022)
Adolescence is a period of very rapid change, both in terms of physical changes and changes in attitudes and behavior.Nutritional needs are one of the factors that affect the development of a teenager.Suboptimal nutrition will affect health and increase the risk of infectious and non-communicable diseases such as cardiovascular disease (heart and blood vessel disease, hypertension and stroke), diabetes and cancer which are the main causes of death in Indonesia.This study aims to determine the relationship between knowledge and nutrient intake with the nutritional status of students at SMAN 12 Kupang City.This study aims to identify the relationship between knowledge and nutrient intake with the nutritional status of students at SMAN 12 Kupang City. This type of research is a quantitative study with a cross sectional design. Based on the results of the Chi-Square test, it shows that there is no relationship between knowledge and nutritional status of students (p = 0.209), there is no relationship between energy intake and nutritional status of students (p = 0.573), there is no relationship between protein intake and nutritional status. students (p = 0.317), there is a relationship between fat intake and the nutritional status of students (p = 0.012), there is no relationship between carbohydrate intake and the nutritional status of students (p = 0.538), there is no relationship between vitamin A intake and student nutritional status (p = 0.538). p = 0.626), there is no relationship between nutrient intake and nutritional status of students (p = 0.202).